A Review of Allogeneic Hematopoietic Stem Cell Transplantation in Metastatic Breast Cancer - Nuri Karadurmus (International Journal of Hematology-Oncology and Stem Cell Research, 2018)
Breast cancer (BC) has a high mortality rate and metastatic BC is almost incurable despite hormonal therapy and chemotherapy. The second and third lines of chemotherapies usually yield transient responses and the median survival is generally as low as 18-24 months. Autologous and allogeneic hematopoietic stem cell transplantation (HSCT) have been extensively investigated in this setting. The presence of immune mediated anti-tumor effects referred to as graft-versus-tumor (GvT) effects after allogeneic HSCT among patients with solid tumors have been clearly defined. The advantages of allogeneic HSCT over autologous HSCT for metastatic BC are i) cancer-free graft and ii) immune-mediated GvT effects mediated by human leukocyte antigen compatible donor T-cells. In conclusion, a GvT effect does exist against metastatic BC and play a key role in tumor response. This review aims to describe the background, rationale, and clinical results of allogeneic HSCT as a potential alternative treatment in metastatic BC.